Preliminary In Vivo Evaluation of a Hybrid Armored Vascular Graft Combining Electrospinning and Additive Manufacturing Techniques - Spadaccio, Cristiano (Drug Target Insights, 2016)
In this study, we tested in vivo effectiveness of a previously developed poly-l-lactide/poly-ε-caprolactone armored vascular graft releasing heparin. This bioprosthesis was designed in order to overcome the main drawbacks of tissue-engineered vascular grafts, mainly concerning poor mechanical properties, thrombogenicity, and endothelialization. The bioprosthesis was successfully implanted in an aortic vascular reconstruction model in rabbits. All grafts implanted were patent at four weeks postoperatively and have been adequately populated by endogenous cells without signs of thrombosis or structural failure and with no need of antiplatelet therapy. The results of this preliminary study might warrant for further larger controlled in vivo studies to further confirm these findings.